Protective Effects of Aryl Hydrocarbon Receptor Signaling in Celiac Disease Mucosa and in Poly I:C-Induced Small Intestinal Atrophy Mouse Model - Dinallo, Vincenzo; Marafini, Irene; Di Fusco, Davide; Di Grazia, Antonio; Laudisi, Federica; Dwairi, Rami; Paoluzi, Omero A.; Monteleone, Giovanni; Monteleone, Ivan (Frontiers in Immunology, 2019)
Aryl hydrocarbon receptor (AhR), a transcription factor activated by a large number of natural and synthetic agents, modulates the activity of immune cells in the gut and represents an important link between the environment and immune-mediated pathologies. In this study, we investigated the role of AhR in celiac disease (CD), a gluten-driven enteropathy. AhR expression was evaluated in intestinal biopsies taken from patients with CD and controls by real-time polymerase chain reaction (PCR), immunohistochemistry and flow cytometry. AhR was also analysed in ex vivo organ cultures of duodenal biopsies taken from inactive CD patients incubated in presence or absence of peptic-tryptic digest of gliadin. IFN-γ, TNF-α, granzyme B and perforin expression was evaluated in anti-CD3/CD28-activated intestinal lamina propria mononuclear cells (LPMC) and intestinal intra-epithelial cells (IEL) of active CD patients cultured in the presence or absence of the AhR agonist 6-formylindolo(3, 2-b)carbazole (Ficz). Finally, the protective role of AhR was evaluated in a mouse model of poly I:C-driven small intestine atrophy. AhR RNA transcripts were reduced in active CD samples as compared to inactive CD and normal controls. Flow cytometry confirmed such results and showed a reduction of AhR in both IEL and LPMC of active CD patients. The addition of a peptic-tryptic digest of gliadin to ex vivo organ cultures of duodenal biopsies taken from inactive CD patients reduced AhR expression. Treatment of CD IEL and LPMC with Ficz reduced the levels of inflammatory cytokines, granzyme B and perforin. Mice injected with Ficz were protected against poly I:C-induced villous atrophy. Our findings suggest that defective AhR-driven signals could contribute to amplify pathogenic responses in the gut of CD patients.